1990
DOI: 10.1002/art.1780330706
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro effects of methotrexate on peripheral blood mononuclear cells: Modulation by methyl donors and spermidine

Abstract: The mode of action of low-dose methotrexate (MTX) in rheumatoid arthritis (RA) is unclear. The effects of MTX are mediated primarily through inhibition of dihydrofolate reductase, resulting in a dosedependent inhibition of purine and pyrimidine synthesis. Other folate-dependent metabolic pathways might be secondarily affected. One such pathway is the regeneration of methionine from homocysteine, with subsequent formation of the methyl donor S-adenosylmethionine (SAM) and polyamines, which are important in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 28 publications
1
26
0
3
Order By: Relevance
“…This suggests that exposure to MTX may induce some type of anergy. Interestingly, MTX has been associated with many other functional attributes such as suppressing neutrophil chemotaxis [26], inhibiting interleukin (IL)-1 activity [27], IL-6 production [28], IL-4, IL-13, interferon-g, tumour necrosis factor-a and granulocyte-macrophage colonystimulating factor [29], as well as reducing immunoglobulin levels [30][31][32]. In addition, MTX has been associated with increased adenosine release [33] and inhibiting cyclooxygenase-2 activation [34] and lymphocyte proliferation [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that exposure to MTX may induce some type of anergy. Interestingly, MTX has been associated with many other functional attributes such as suppressing neutrophil chemotaxis [26], inhibiting interleukin (IL)-1 activity [27], IL-6 production [28], IL-4, IL-13, interferon-g, tumour necrosis factor-a and granulocyte-macrophage colonystimulating factor [29], as well as reducing immunoglobulin levels [30][31][32]. In addition, MTX has been associated with increased adenosine release [33] and inhibiting cyclooxygenase-2 activation [34] and lymphocyte proliferation [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Increased polyamine concentrations are found in urine, synovial fluid, synovial tissue, and peripheral blood mononuclear cells from patients with rheumatoid arthritis (Hawkes et al, 1994), and the accumulated polyamines may be metabolized by monocytes to form, among other molecules, NH 3 and H 2 O 2 , which may be toxic to lymphocytes (Talal et al, 1988;Flescher et al, 1989Flescher et al, , 1992Nesher and Moore, 1990;Yukioka et al, 1992;Furumitsu et al, 1993;Nesher et al, 1996). By inhibiting dihydrofolate reductase, methotrexate inhibits the formation of tetrahydrofolate which donates a methyl group during the synthesis of methionine from homocysteine ( Fig.…”
Section: B Inhibition Of Spermine and Spermidine Productionmentioning
confidence: 99%
“…An alternative pathway by which methotrexate could modulate inflammatory cell interactions is suggested by studies of Nesher and Moore (32), who found that methionine reverses the effects of methotrexate on in vitro immunoglobulin production and hypothesized that uptake of methionine leads to regeneration of S-adenosylmethionine, a methyl donor that may be depleted in methotrexate-treated cells due to inhibition of dihydrofolate reductase. Our results do not exclude the hypothesis of Nesher and Moore (32) but suggest an alternative interpretation of their studies.…”
Section: CImentioning
confidence: 99%